Early protoneutron star deleptonization - consistent modeling of weak processes and equation of state. Issue 1 (January 2016) - Fischer, T; Huther, L; Lohs, A; Martínez-Pinedo, G
Abstract: We discuss the impact of consistent modeling of weak processes and nuclear equation of state (EOS) during the deleptonization phase of protoneutron stars (PNS). They are born in the event of a core-collapse supernova. Being initially hot and lepton rich, PNSs deleptonize via the continuous emission of neutrinos of all flavors. Unlike during the mass accretion phase prior to the onset of the supernova explosion, when the neutrinospheres are located at low densities, they shift to significantly higher densities during the PNS deleptonization phase after the supernova explosion has been launched. Important during this phase is the inclusion of medium modifications to the weak processes, which depend on the nuclear EOS. In particular, these medium modifications depend on the nuclear symmetry energy and its density dependence. We discuss two selected nuclear models and illustrate the early PNS deleptonization phase for a particular EOS. As has been realized recently, including weak processes consistently with the EOS increases the spectral differences of ve and in comparison to simulations that neglect the underlying medium modifications. This has important consequences for the nucleosynthesis relevant conditions of the ejecta as well as for potential neutrino flavor oscillations and hence detection on Earth.